2018
DOI: 10.3892/mco.2018.1786
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and therapeutic role of HER2 expression in micropapillary carcinoma of the bladder (Review)

Abstract: Micropapillary carcinoma of the bladder (MPBC) is a variant type of infiltrating urothelial carcinoma, which portends a poor biological behavior in terms of disease stage at first diagnosis and clinical outcome; its peculiar morphology raises issues concerning the ability of tumor detection by imaging techniques and proper biopsy procedure, and the appropriate treatment for non-muscle infiltrating and muscle-infiltrating MPBC remains a matter of debate. On the basis of its established prognostic and therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 103 publications
(165 reference statements)
0
24
0
Order By: Relevance
“…Micropapillary and sarcomatoid variations may lead to poor oncology outcomes ( 30 ). Another study also suggested that the micropapillary variation often predicts a poor biological behavior in invasive urothelial carcinoma of the bladder ( 31 ). This phenomenon may be related to the overexpression of HER2 protein, but this result needs to be confirmed in a larger, multi-institutional study.…”
Section: Discussionmentioning
confidence: 99%
“…Micropapillary and sarcomatoid variations may lead to poor oncology outcomes ( 30 ). Another study also suggested that the micropapillary variation often predicts a poor biological behavior in invasive urothelial carcinoma of the bladder ( 31 ). This phenomenon may be related to the overexpression of HER2 protein, but this result needs to be confirmed in a larger, multi-institutional study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, further analyses are needed to assess the correlation between tumor MUC1 expression and CA 15-3 serum levels in patients with advanced MPUC. Recently, several studies have proposed potential biomarkers for MPUC such as human epidermal growth factor receptor-2 overexpression [ 10 ] and miR-296 and RUVBL1 activation [ 11 ]. Although these candidates are potentially useful for screening and follow-up in patients with MPUC in the future, they are currently not easy to measure in clinical practice.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Low-grade carcinomas can be characterized at the molecular level by loss of heterozygosity (LOH) of chromosome 9 and activating mutations of genes encoding fibroblast growth factor receptor 3 (FGFR3) and telomerase reverse transcriptase (TERT), while MIBC is thought to arise via flat dysplasia and Tis (5). The human epidermal growth factor receptor-2 (HER2) has been reported with overexpression among aggressive BCa for the past decade, suggesting that this biomarker might aid in patient risk stratification and treatent selection (150,151). Ferro et al reported that absolute basophil count is closely related to time to recurrence among patients with high-grade T1 BCa receiving BCG after TURBT (152).…”
Section: Fully Using Vi-rads For Bca Phenotype Prediction and Recurrence Risk Stratificationmentioning
confidence: 99%